Multicultural Transformation in Waqf Land Registration: Role of Waqf Pledge Deed Officials in Manado, Indonesia - Lahilote, Hasyim Sofyan; Subeitan, Syahrul Mubarak (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2024)
This study explores the multicultural transformation in waqf land registration in Indonesia, focusing on the role of Waqf Pledge Deed Officials (PPAIWs) in Singkil District, Manado City. Employing a multicultural approach integrated with empirical legal research methods, this study examines how national waqf policies interact with cultural and religious diversity at the local level. Data collection methods include legal document analysis, field observations, and in-depth interviews with PPAIWs, nazhirs, religious leaders from various communities, and government officials. The data were analyzed using a multicultural theoretical framework, emphasizing the concepts of 'interactive multiculturalism' and 'dialogical multiculturalism'. The findings reveal that only 18.9% of waqf lands are certified and 21.6% have Waqf Pledge Deeds, reflecting the challenges in aligning national policies with local multicultural realities. However, the adaptive strategies of PPAIWs in bridging cultural and religious differences demonstrate the potential for multicultural transformation in waqf management. This study proposes a more inclusive model of waqf registration, including cross-cultural outreach programs, flexible legal interpretations, and the utilization of interfaith dialogue. This research contributes to a more nuanced understanding of religious law implementation in pluralistic societies, offering new insights into how waqf policies can be enriched through a multicultural approach to enhance social harmony and administrative effectiveness.